(3CfS GdefgL hQhV GdaQLs - (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s
(3ChdgG (B:s
(3SGeM GddahX hhGgH GdMXhX EdN s
(3JMJhi Ydi NQGFW hCTcGd edhfIs
(3Vefg CbhGd GdLZQGajjf GdSGHbjf eKd HWdjehS hCQSjhS hNGeGN hGHf NQOGP HI hGHf Mhbd hZjQges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B23 - (3U (B558 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs